Convenient stereocontrolled amidoglycosylation of alcohols with acetylated glycals and trichloroethoxysulfonamide. (3rd November 2016) - Murakami, Teiichi; Sato, Yukari; Yoshioka, Kyoko; Tanaka, Mutsuo
Abstract: A regio- and stereo-controlled, rhodium(II)-catalyzed amidoglycosylation of alcohols has been developed using O -acetylated glycals, trichloroethoxysulfonamide, and iodosobenzene. This one-pot amidoglycosylation was applied to a variety of primary and secondary alcohols to afford the β- O -glycosides with acceptable yields up to 84%. The reaction would proceed via stereoselective intermolecular aziridination of the glycal from the α-face followed by SN 2 reaction with alcohol at C-1 from the β-face to give 1, 2:2, 3-di- trans -substituted isomer only. Graphical abstract: Highlights: A regio-controlled one-pot synthesis of 2-deoxy-2-sulfonamino-1- O -glycosides from acetylated glycals. 1, 2:2, 3-Di- trans -substituted glycosides were formed in a stereospecific manner. This amidoglycosylation was applied to a variety of primary and secondary alcohols. The reaction would proceed via rhodium(II)-catalyzed intermolecular aziridination with a sulfonyl-nitrene.